Review on Performance Measurement Systems - Sorooshian, Shahryar; Nor Fillianie, Aziz; Asraf, Ahmad; Syafiah Norsyahira, Jubidin; Nor Mahirah, Mustapha (MCSER Publishing, 2016)
the organization performance. PMS create a very significant connection among organizations due to measurement in the organization system directly related to the organization strategy. A well develop and implementation of comprehensive PMS helps the organization to develop and improvise the business environment thus improve better decision making process. Therefore, there are multi comprehensive approaches of PMS has been applied in both quantitative and qualitative are significant to measure, predict and evaluate on current and future organization performance. The adoption of difference models has had on various dimension and measure give the difference result of organization performance. Therefore, this paper discuss on the different PMSs which have been developed to be use in companies. As one of the first comprehensive attempts in performance management area, in this article almost all popular PMSs have being reviewed; PSMs such as Balanced Scorecard, Performance Prism, Performance Measurement Matrix, Strategic Measurement and Reporting Technique, European Foundation for Quality Management and Theory of Constraints, Result and Determinant, Integrated Performance Measurement for Small Firms, Integrated PMS, Organizational Performance Measurement, Dynamic Multi-Dimensional Performance Framework, Integrated Dynamic PMS, Holistic Performance Management, Medori and Steeple Framework and Qualitative Performance. Many of company managers has their own preferable performance management but least number of them are aware of different available PSMs. However, this paper found some of most favorable PMSs developed for adaptation by the organization recently; and concludes with a need for a comprehensive model.